Private sector participation in water infrastructure : OECD checklist for public action. (OECD studies on water., 2009)
Many countries have sought the involvement of the private sector to upgrade and develop their water and sanitation infrastructure and improve the efficiency of water systems. This book provides a catalogue of policy directions, including appropriate allocation of roles, risks and responsibilities, framework conditions and contractual arrangements necessary to make the best of private sector participation and to harness more effectively the capacities of all stakeholders.--Publisher's description.